Perbandingan Holt’ Method dan Winter’s Method pada Peramalan Ekspor Minyak dan Gas Bumi di Indonesia - Darmansah Darmansah Darmansah; M. Yoka Fathoni; Ade Tiara Rosalinda; Miftahul Jannah; Pero Roberto Kristovic (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Oil and natural gas are Indonesia's main sources of income. In terms of natural gas reserves, Indonesia ranks fourteenth in the world. So that to stabilize the country's economy, one of the things that can be done is international trade. However, as time goes by, exports of natural oil and natural gas are decreasing, so that we as exporters of oil and gas (natural oil and gas) must be able to forecast demand correctly so that it is easy to make decisions and not have a bad impact on operating costs. To overcome this, a forecasting comparison is carried out using the Holt' Method and also the Winter;s Method to find which method produces the smallest error value. To assess the accuracy of the results of forecasting using the Mean Absolute Prcentage Error (MAPE). Actual data on oil and gas exports were taken from 2017 to the first quarter of 2021. The results of forecasting using the Winter's Method in 2021 quarters 2, 3, and 4 respectively were 1659.44; 1731.5; and 1813.27 million Dollars with a MAPE error rate of 12.82%. Meanwhile, using the Holt' Method, the results of forecasting in the second quarter of 2021 are 2694.94 million Dollars with a MAPE error rate of 15.78%.